2021
DOI: 10.1186/s12864-021-08134-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of the xyloglucan endotransglucosylase/hydrolase gene family in poplar

Abstract: Background Xyloglucan endotransglucosylase/hydrolase (XTH) family plays an important role in cell wall reconstruction and stress resistance in plants. However, the detailed characteristics of XTH family genes and their expression pattern under salt stress have not been reported in poplar. Results In this study, a total of 43 PtrXTH genes were identified from Populus simonii × Populus nigra, and most of them contain two conserved structures (Glyco_h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 68 publications
3
32
2
Order By: Relevance
“…For example, the genes from the ancestral group and Group III were localized in the extracellular space and cell wall, respectively, whereas genes in Group I/II were mainly in the cell wall, cytoplasm, and extracellular space. These findings were similar to those reported in pineapple and poplar ( Li et al, 2019 ; Cheng et al, 2021 ). Moreover, all the genes in Group III contained three introns and four exons, and the types and numbers of conserved motifs within the group were similar.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For example, the genes from the ancestral group and Group III were localized in the extracellular space and cell wall, respectively, whereas genes in Group I/II were mainly in the cell wall, cytoplasm, and extracellular space. These findings were similar to those reported in pineapple and poplar ( Li et al, 2019 ; Cheng et al, 2021 ). Moreover, all the genes in Group III contained three introns and four exons, and the types and numbers of conserved motifs within the group were similar.…”
Section: Discussionsupporting
confidence: 92%
“…Segmental and tandem duplication events did not lead to XTH gene family expansion but might increase functional divergence, which was an essential factor in adapting to environmental changes ( Conant and Wolfe, 2008 ). Of course, segmental and tandem duplication events also are found among poplar XTH family genes ( Cheng et al, 2021 ). Furthermore, the phylogenetic analysis of XTH encoded proteins among the five plants revealed that S. superba and C. sinensis , all belonging to Theaceae, had many more genetic relationships, while Populus and E. grandis had much closer relationships ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, these genes play an important role in cell wall reconstruction and stress resistance, particularly abiotic stresses. Thirty-five XTH genes have been reported in sorghum [ 17 ]. To the best of our knowledge, no biotic stress related function has been reported, suggesting that this SNP association could be due to switching to the flooded environment to which the seedlings were exposed during the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, the XTH family has been identified and analyzed in species such as Arabidopsis thaliana (33), Hordeum vulgare (24), Glycine max (61), and Nicotiana tabacum (54). ( Nomchit et al, 2010 ; Li et al, 2018 ; Meng et al, 2018 ; Cheng et al, 2021 ; Strohmeier et al, 2004 ; Tiika et al, 2021 ). The XTH family was initially classified into three groups, named groups I, II, and III, in Arabidopsis ( Campbell & Braam, 1999 ).…”
Section: Introductionmentioning
confidence: 99%